The view from the streets - Hasan, Vahisha (Review and expositor, 2020)
This article offers a view of the impact of Dr. James Cone's Black liberation theology on faith-based social action from an orientation of front-line activism of people of faith. The significance of the southern United States and the founding/founders of the Black Lives Matter movement are two examples through which the article explores this impact. Six questions posited by theologian Diana Hayes, as well as the liberatory possibilities in their answers, are crucial for the front-line activism of tomorrow.